Garrido, Álvaro e David J. Starkey (eds) (2020) Too Valuable to be Lost – Overfishing in the North Atlantic since 1880 (Edited by Álvaro Garrido and David J. Starkey) - Carreto, Carlos (2021)
UIDB/00657/2020 UIDP/00657/2020